Apropriações ativistas em sites de redes sociais: cartografia das ações coletivas no twitter - Batista, Jandré Corrêa (2012)
For a long time in history, forms of communication of social movements were restricted to the notion of face to face interaction. As the media evolved, new perspectives emerged for the benefit of the ways of communication of the movement and the expansion strategies of persuasion. Both expanding activist s audience and creating new ways to act collectively, the activist appropriation of communication resources is characterized as a natural tendency to the people empowered protest. The present dissertation is about the appropriation of the microblog Twitter (twitter.com) for political purposes. For that, we intend to make the firsts draws, considering the cartographic perspective (Deleuze and Guattari, 1995), about the appropriation of this specific social networking site (Boyd and Ellison, 2006) for activism, considering collective actions such as #wikileaks, #iranelection , #occupy and #forasarney movement, among others.